2021
DOI: 10.1038/s41598-021-98925-6
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology-based investigation of potential targets of astragalus membranaceous-angelica sinensis compound acting on diabetic nephropathy

Abstract: To explore the mechanism of the Astragalus membranaceous (AM)-Angelica sinensis (AS) compound in the treatment of diabetic nephropathy (DN) we used network pharmacology and molecular docking. Screen the components and targets of the AM-AS compound in the TCMSP and the BATMAN-TCM, and establish a component-target interaction network by Cytoscape 3.7.2. After searching relevant targets of DN in related databases, the common targets of the AM-AS compound and DN were obtained by comparison. Gene ontology (GO) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…The docking score values determine the binding potential or affinity of drugs to their targets, as well as the stability of conformations. A docking score value of less than −7 indicates strong binding activity, values between −5 and −7 demonstrate good binding activity, and values in the range of −4.25 to −5 signify a certain binding activity ( Dong et al, 2021 ). Out of 40 core targets, we selected 11 proteins involved in different mechanisms to perform docking with the top 21 MA compounds (with ≥40) in terms of degree.…”
Section: Resultsmentioning
confidence: 99%
“…The docking score values determine the binding potential or affinity of drugs to their targets, as well as the stability of conformations. A docking score value of less than −7 indicates strong binding activity, values between −5 and −7 demonstrate good binding activity, and values in the range of −4.25 to −5 signify a certain binding activity ( Dong et al, 2021 ). Out of 40 core targets, we selected 11 proteins involved in different mechanisms to perform docking with the top 21 MA compounds (with ≥40) in terms of degree.…”
Section: Resultsmentioning
confidence: 99%
“…e primary pathogenesis of "Xiaoke" is spleen deficiency, the root pathogen is a lack of Qi spirit, and blood stasis is implicated during the entire course of diabetes. In clinical treatment, P. ginseng, a Qi-tonifying herb, is used in combination with other T2DM treating herbs, such as "white tiger plus ginseng," to invigorate the Qi [27,28]. e antihyperglycemic effect of P. ginseng has also been demonstrated by previous in vitro, in vivo, and clinical trial studies [6].…”
Section: Discussionmentioning
confidence: 95%
“…We docked the core targets IL2 (PDB ID : 1M48), BCHE (PDB ID : 6EQP), AKT1 (PDB ID : 3OS5), and LGALS3 (PDB ID : 6Q17) with the key active ingredients; the lower the binding energy, the better the combination of the two. Studies have shown that affinity lower than −4.25 kcal/mol hasa certain binding force, the affinity lower than −5.0 kcal/mol has a good binding force, and the affinity lower than −7.0 kcal/mol has a strong binding force [40,41]. e results showed that all key active ingredients had a good binding ability to the core targets (Table 1).…”
Section: Molecular Dockingmentioning
confidence: 94%